Four Keggin-type polyoxometalate-based complexes derived from bis(pyrazine)–bis(amide) ligands for electrochemical sensing of multiple analytes and adsorbing dye molecules. Issue 4 (4th January 2022) - Cui, Zi-Wei; Lu, Jun-Jun; Lin, Hong-Yan; Luan, Jian; Chang, Zhi-Han; Li, Xiao-Hui; Wang, Xiu-Li
Abstract : Four new Keggin-based complexes derived from bis(pyrazine)–bis(amide) ligands are used to detect multiple analytes (BrO3 − NO2 −, Cr(vi ) and Fe(iii ) ions) and adsorb organic dye molecules from aqueous solution. Abstract : Four new Keggin-type polyoxometalate (POM)-based metal–organic complexes constructed from two flexible bis(pyrazine)–bis(amide) ligands N, N ′-bis(2-pyrazinecarboxamide)-1, 2-ethane (bpae) and N, N ′-bis(5-methyl-2-pyrazinecarboxamide)-1, 2-ethane (bmpae), namely, [Cu2 (bpae)2 (H2 O)2 (PMo VI 9 Mo V 3 O39 )]·5.5H2 O (1 ), [Cu2 (bpae)2 (SiMo12 O40 )]·3H2 O (2 ), {[Co2 (bmpae)2 (H2 O)4 ](SiW12 O40 )}·1.5H2 O (3 ), and [Cu2 (bmpae)2 (SiW12 O40 )]·8H2 O (4 ), have been hydrothermally synthesized and structurally characterized. Complex 1 is a [PMo VI 9 Mo V 3 O39 ] 4− (PMo12 )-based 3D coordination framework, which is constructed by three kinds of 1D chains: [Cu(bpae)] n 2 n +, [PMo12 ] n 4 n − and [Cu(PMo12 )] n 2 n − chains. Complex 2 shows a 2D structure, which is composed of tridentate [SiMo12 O40 ] 4− anions (SiMo12 ) and [Cu(bpae)] n 2 n + chains. Complex 3 is a 0D structure, which is constructed from [Co2 (bmpae)2 ] 4+ binuclear rings and discrete [SiW12 O40 ] 4− (SiW12 ) anions. In 4, the 1D [Cu(bmpae)] n 2 n + chains are connected by the SiW12 anions to produce a 2D structure. The diverse structures of 1–4 demonstrate that the different metal ions and POMs have pivotal influences on the formation of the final coordination frameworks. In this work, the adsorption performances of 1–4 for the organic dyes gentian violet (GV) and methylene blue (MB) were examined, and 1 possesses good reusability. In addition, 1–4 can be employed as amperometric sensors to identify multiple analytes (BrO3 −, NO2 −, Cr(vi ) and Fe(iii ) ions) and possess good selectivity in the presence of some other ions.